2015
DOI: 10.1111/joic.12210
|View full text |Cite
|
Sign up to set email alerts
|

Stenting and Adjunctive Delivery of Paclitaxel Via Balloon Coating Versus Durable Polymeric Matrix for De Novo Coronary Lesions: Clinical and Angiographic Results from the Prospective Randomized Trial

Abstract: Paclitaxel delivery via drug coated balloon or polymer-stent matrix achieved comparable angiographic and clinical results among patients with de novo coronary lesions. BMS + PCB revascularization was associated with a higher rate of stent thrombosis when compared to newer generation drug eluting stents, therefore, should be recommended as a bail-out for PCB alone angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Vascular enlargement after a "paclitaxel-coated balloon only" approach for de novo coronary stenosis has been demonstrated [20,21]. Thus, our results give the pathophysiological clue (focal positive vessel remodeling) for the increased stent thrombosis rates after BMS/PCB as previously published [13]. Furthermore, the reversibility of the observed positive remodeling after a BMS/PCB procedure.…”
Section: Incomplete Stent Apposition and Positive Vessel Remodelingsupporting
confidence: 72%
“…Vascular enlargement after a "paclitaxel-coated balloon only" approach for de novo coronary stenosis has been demonstrated [20,21]. Thus, our results give the pathophysiological clue (focal positive vessel remodeling) for the increased stent thrombosis rates after BMS/PCB as previously published [13]. Furthermore, the reversibility of the observed positive remodeling after a BMS/PCB procedure.…”
Section: Incomplete Stent Apposition and Positive Vessel Remodelingsupporting
confidence: 72%
“…Following screening for replicates, 405 remained; and after screening abstracts for relevance, a further 371 studies were removed. Finally, full text of the remaining 34 studies were screened, of which 17 randomised controlled trials (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) fulfilled the inclusion criteria and were qualitatively and quantitatively analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, any future studies of DEB must be against the latest generation of DES so that a valid comparison can be made against the technology in current clinical use. Finally, some studies were susceptible to industry bias owing to author involvement in relevant device companies such as B. Braun, Boston Scientific Medtronic and Eurocor GmbH (18,21,22,28,29,31,33). Similarly, conflicts of interest may have arisen due to these companies funding studies which investigated their own products (18,21,26,28,30,31,33,34).…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, none of the studies included ST as a primary endpoint. Table S1 in the appendix illustrates that only the study by Żurakowski et al [27] and PEPCAD I [37] found an excess of late ST in the DES group after a clinical follow-up of 9 and 6 months, respectively. However, Żurakowski et al found more ST in the BMS + DEB arm in total as a result of more early ST in this group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PERfECT stent study [24, 25] showed that DEB in combination with an EPC stent was better than EPC stent alone; however, these findings were not supported by the PEGASUS study [26]. However, when DEB + BMS are compared to DES, at best similar results have been reported [27], but most studies have found the combination of DEB + BMS inferior to DES. Thus, by using optical coherence tomography the OCTOPUS trial found that DEB + BMS was associated with more pronounced neointimal proliferation than DES [28, 29], while the IVUS study used intravascular ultrasound to show more pronounced neointimal hyperplasia in the DEB + BMS group leading to more revascularizations than in the DES group [30].…”
Section: Drug-eluting Balloonsmentioning
confidence: 99%